IMPLEMENTASI KURIKULUM BERBASIS ENTREPRENEURSHIP UNTUK MENCETAK GENERASI PENGUSAHA DALAM MENGHADAPI BONUS DEMOGRAFI - Rita Meiriyanti; Aprih Santoso (STIE Pelita Nusantara Semarang, 2017)
The unemployment rate in Indonesia based on the data from the Central Bureau of Statistics in 2016 was 5.5%. This number raised concerns since it shows how ready younger generation is to face global competition. Demographic bonus between 2020 and 2030 make the problem even bigger if our goverment and private sector cannot make enough job opportunity for young generation. Entrepreneurship is the solution to create new job opportunities and open the way for Indonesian to get economic sovereignity and become host in their own country. The university should be more proactive in supporting entrepreneurship-based curriculum by giving direct assistance from the college or utilize entrepreneurship center, not only based on course.The purpose of this research is to find the implementation model of entrepreneurship-based curriculum program that can create the mindset of the educated people from Job Seeker into Job Creator. The research design used is qualitative method with phenomenology approach and the participant is a group of objects used as data source that is students of Universitas Semarang.The result of the research shows that the entrepreneurship-based curriculum implementation model will strengthen the position of universities as one of the leading mediators and facilitators in building the young generation of the nation has the obligation to teach, educate, train and motivate the students to become intelligent generation that is independent, creative, innovative and capable Creating various job opportunities (business). With the paradigm of change that gave birth to young entrepreneurs-successful entrepreneurs like